Critical Psychiatry - Middleton, Hugh (Pavilion Publishing, 2007)
Critical psychiatry appraises and comments upon psychiatric services as they are usually provided. This article, prompted by the publication of a recent book, considers the place of critical psychiatry historically and in the context of contemporary mental health care and treatment.